Influence of Dietary Bacillus Sp. Fermented Shrimp Waste on Broiler Meat Quality - Hardini, Dini; Djunaidi, Irfan H. (International Journal of Poultry Science, 2010)
An experiment was conducted to evaluate the effect of the inclusion of different levels of Fermented with Bacillus sp. Shrimp Waste Meal (FSWM) in diets on meat quality of broilers. A total of 75 d-old chicks were randomized in 5 (five) treatments with 3 replicate pens of 5 birds each. Treatments consisted of FSWM inclusion of 0 (control) and 5, 7.5, 10 and 12,5% in the diets. Birds were raised under standard condition and provided with feed and water ad-libitum. Feed and birds were weighed weekly up to 35 days and in the end of experimental period, the birds were sacrificed dan dress up to determine meat quality. The texture, lightness, redness and yellowness values of breast meat were increased and cooking loss and water holding capacity were decreased. The pH, water and ash content of breast meat was similar for all treatment, fat content was decreased and protein content was increased as compared to the control. The present result indicated that FSWM be potential feed ingredient to supply part of dietary protein requirement of broiler without any differences in broiler meat quality.